Factors Affecting Food Security of Expropriated Peri-Urban Households in Ethiopia: The Case of the East Gojjam Administrative Zone - Moges Wubet Shita; Sayeh Kassaw Agegnehu; Derjew Fentie Nurie; Tilahun Dires; Gerhard Navratil (Land)
Food insecurity in peri-urban areas is exacerbated by high living costs, limited access to healthy food, and economic inequality. Despite its growing prevalence due to factors like land loss from urban expansion, food insecurity has received limited attention. In Ethiopia, drastic urbanization creates competition for land between agriculture and urban development, which is becoming extreme in peri-urban areas., This study aims to assess the impact of urban expansion on food security among expropriated peri-urban households in Ethiopia. Using a calorie intake-based food security line, we categorize respondents as food-secure or -insecure. The research analyzed data from 350 expropriated peri-urban households through a structured questionnaire, employing descriptive statistics and binary logistic regression. About 67% of the respondents were classified as food-insecure. The binary logit model identified several significant determinants of food security, including compensation amount and type, household head demographics, agricultural land rent participation, irrigation and credit access, off-farm income, and organic fertilizer use. To address food insecurity among expropriated households, policymakers must prioritize these factors. Government attention and policy consideration are crucial to ensure the well-being of these vulnerable populations.